Improved Efficiency of Intraventricular Blood Flow Transit Under Cardiac Stress: A 4D Flow Dobutamine CMR Study - Sundin, Jonathan; Engvall, Jan; Nylander, Eva; Ebbers, Tino; Bolger, Ann F.; Carlhäll, Carl-Johan (Frontiers in Cardiovascular Medicine, 2020)
Introduction The effects of heart rate, inotropy and lusitropy on multidimensional flow patterns and energetics within the human heart remain undefined. Recently, reduced volume and end-diastolic kinetic energy (KE) of the portion of left ventricular (LV) inflow passing directly to outflow, Direct flow (DF), have been shown to reflect inefficient LV pumping and to be a marker of LV dysfunction in heart failure patients. In this study, we hypothesized that increasing heart rate, inotropy and lusitropy would result in an increased efficiency of intraventricular blood flow transit. Therefore, we sought to investigate LV 4D blood flow patterns and energetics with dobutamine infusion. Methods 4D flow and morphological cardiovascular magnetic resonance data were acquired in twelve healthy subjects: at rest and with dobutamine infusion to achieve a target heart rate approximately 60% higher than the resting heart rate. A previously validated method was used for flow analysis: pathlines were emitted from the end-diastolic (ED) LV blood volume and traced forward and backward in time to separate four functional LV flow components. For each flow component, KE/mL blood volume at ED was calculated. Results With dobutamine infusion there was an increase in heart rate (64%, p<0.001), systolic blood pressure (p=0.02) and stroke volume (p=0.01). Of the 4D flow parameters, the most efficient flow component, (DF), increased its proportion of EDV (p<0.001). The EDV proportion of Residual volume, the blood residing in the ventricle over at least two cardiac cycles, decreased (p<0.001). The KE/mL at ED for all flow components increased (p<0.001). DF had the largest absolute and relative increase while Residual volume had the smallest absolute and relative increase. Conclusions This study demonstrates that it is feasible to compare 4D flow patterns within the normal human heart at rest and with stress. At higher heart rate, inotropy and lusitropy, elicited by dobutamine infusion, the efficiency of intraventricular blood flow transit improves, as quantified by an increased relative volume and pre-systolic KE of the most efficient DF component of the LV volume. The change in these markers may allow a novel assessment of LV function and LV dysfunction over a range of stress.